1995
DOI: 10.1093/geront/35.4.560
|View full text |Cite
|
Sign up to set email alerts
|

Service Directories: Reinvigorating a Community Resource for Self-Care

Abstract: This article reviews the development, distribution, and effectiveness of a free, comprehensive mass-mailed community service directory designed for older people. While only half of a pre/post-distribution sample remembered receiving it, recipients of the directory indicate it increased service awareness and prompted various types of use. Alternatives for design and distribution of community directories are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…The directory seems to be of more interest to women than men, and to those with plans to increase their physical activity levels. The results are consistent with those reported by Cherry et al (1995) and Neuhauser (1998), which suggest that a directory can help to raise people's awareness of local options. 8,9 There were also clear differences associated with the different distribution methods.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The directory seems to be of more interest to women than men, and to those with plans to increase their physical activity levels. The results are consistent with those reported by Cherry et al (1995) and Neuhauser (1998), which suggest that a directory can help to raise people's awareness of local options. 8,9 There were also clear differences associated with the different distribution methods.…”
Section: Discussionsupporting
confidence: 91%
“…Queensland has reported that there is limited awareness of physical activity options in Queensland and recognises a need to provide this information to local communities. 7 While there have been several studies of the effectiveness of directories in terms of improving knowledge and awareness of health services (for example, an increase in participants attending a service, 8 raised awareness about local community services 9 and utilising resources to inform GP choice 10 ), a review of the literature failed to find any evaluation studies of physical activity directories. One study suggested awareness and knowledge of local physical activity options may increase older people's use of these services, and a PAD could be a stimulus for moving people through the stage of change from considering action to physical activity adoption.…”
Section: Discussionmentioning
confidence: 99%
“…The least effective interventions provide only written materials about the importance of lifestyle and health behaviours or provide service directories (e.g., Cherry, Prebis, & Pick, 1995), encouraging the participants to interpret the material in the context of their own health and life situations, and to translate these materials into action for themselves. These interventions do not capitalize on the power of the peer group to motivate and sustain change efforts, nor do they personalize the intervention.…”
Section: Barriers To Self-carementioning
confidence: 99%
“…Previous research documented some of the effects of mass mail dissemination of this service directory (Cherry et al 1995). Although slightly less than half remembered receiving it through the mail, a large majority of those who did remember it indicated that it increased their awareness of local services.…”
mentioning
confidence: 98%
“…This research examines the characteristics of older people who used an informational resource on community health and human services that was distributed by mass mail. This resource was a comprehensive community service directory compiled by a regional United Way agency and mailed to a majority of the older adult households in one Midwestern metropolitan area (as described by Cherry, Prebis, and Pick 1995). This directory, titled Senior Access Directory, had a low-gloss cover and was the size of a small telephone book, though with heavier-weight paper.…”
mentioning
confidence: 99%